In Vitro Anti-HIV Activity of Rosa centifolia, (Leaves and Roots) Extract on HIV-1UG070 and HIV-1VB59 in TZM-bl and PM1 Cell Lines - Umaru, Isaac John; Akem, Ingwu Joseph; Akafa, Tensaba Andes; Ngbede, Ocheifa Mathew; Oteng, Joseph; Utioukpan, Ashaka Fidelis; Mijinyawa, Aboki Nwunuji; Akam, Odok Endurance; Ekup, Ogholo Ogholo (Darul Yasin Al Sys, 2025)
Human immunodeficiency virus (HIV) infection is still contributing significantly in morbidities and mortalities in the world today, more especially in developing countries. The drugs normally use to reat the infection is costly, toxic, and less effective due to resistance by HIV. In view of that an assessment of In Vitro Anti-HIV Activity of Rosa centifolia, (Leaves and Roots) Extract on HIV-1UG070 and HIV-1VB59 in TZM-bl and PM1 Cell Lines. Thus, the present therapy also has limitations of development of multidrug resistance, with a need for the discovery of novel anti-HIV compounds from plants as a potential alternative in combating HIV disease. Methods: The medicinal plant was tested for entry and replication inhibition against laboratory adapted strains HIV-1IIIB, HIV-1Ada5 and primary isolates HIV-1UG070, HIV-1VB59 in TZM-bl cell lines and primary isolates HIV-1UG070, HIV-1VB59 in PM1 cell lines. The plant extracts were further evaluated for toxicity in HEC-1A epithelial cell lines by trans well epithelial model. Results: The methanolic extracts of Rosa centifolia inhibited laboratory adapted HIV-1 strains (IC80 29.17-78.43μg/ml) and primary isolates (IC80 30.4-118μg/ml) in TZM-bl cells. Conclusion: These active methanolic extracts of Rosa centifolia, (leaves and roots) could be further subjected to chemical analysis to investigate the active moiety responsible for the anti-HIV activity. Methanolic extract of Rosa centifolia was found to be well tolerated maintaining the epithelial integrity of HEC-1A cells in vitro and thus has potential for investigating it further the phytochemical responsible for these activities.